Ecological Assessment of Fish Culture Water Bodies Around Dhaka City, Bangladesh (Bangladesh Journal of Zoology, 2021)
This study was conducted during the period November, 2014 - June, 2015 in two urban fish culture pond, at Kalshi and Namapara area of Dhaka city. These ponds are connected to Baunia canal. Water samples were collected seasonally for water quality and zooplankton analyses. Except DO all other measured water quality parameters (pH, TDS, TSS, total ammonia-N, total nitrite-N, total nitrate-N, total phosphate, total sulphate, alkalinity and hardness) were found higher in water. A total of 10 heavy metals (Zn, Fe, Pb, Cd, Al, As, Cu, Na, Mn and Cr) were measured for determining its concentrations in waters in two seasons. A total of 10 zooplankton species were recorded at Kalshi during the study period and on an average, the density of zooplankton in dry season and in wet season were estimated to be 1386 indiv./L and 244 indiv./L respectively. On the other hand, a total of 19 zooplankton species were identified from Namapara water body and on an average, the density of zooplankton in dry season and in wet season were estimated to be 1760 indiv/L and 343 indiv./L respectively. Bacteriological analysis included the total plate count (TPC), total coliform (TC) and total faecal coliform (TFC) counts in waters, both in wet and dry seasons. In general, water qualities of the studied fish culture water bodies are highly deviated from the permissible standard levels of Environment conservation rules, 1997 and unsuitable for fish culture from fish health point of view. The measured high levels of metals in waters are likely to bioaccumulate in fish body. High abundance of bacterial flora in fish culture waters is also likely to be associated with fish health and may cause enteric diseases. Therefore, fish culture in these urban water bodies is likely pose potential health risks for human through consuming these fishes.Bangladesh J. Zool. 49 (2): 267-276, 2021